High-heat-resistance flame-retardant PC / ABS composite material as well as preparation method and application thereof

Through the combination of phosphorus-based and sulfonate-based flame retardant, a dense carbonized layer is formed, which solves the problem of insufficient flame retardancy of PC/ABS composite materials, significantly improves flame retardant performance and mechanical properties, and ensures the stability of the charging pile. and durability.

CN119286222APending Publication Date: 2025-01-10河南省科学院同位素研究所有限责任公司 +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411567174.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The flame retardant properties of existing PC/ABS composites are poor, especially the flame retardant properties of ABS are insufficient, which leads to dripping and high smoke during combustion, affecting safety, and the phosphorus-based flame retardant used alone, such as BDP, are also used. There are similar problems.

Method used

By combining the phosphorus-based flame retardant and sulfonate-based flame retardant, a dense carbonization layer is formed to block heat and oxygen, reduce toxic fumes and drips, and promote cross-linking reactions through sulfonates to improve flame retardant. Performance and mechanical properties.

Benefits of technology

It significantly improves the flame retardant performance and mechanical properties of the material, ensures the stability and durability of the charging piles in different environments, reaches the UL94 V-0 flame retardant standard, and reduces the concentration of combustible gases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119549630000261
    Figure BDA0005119549630000261
  • Figure BDA0005119549630000271
    Figure BDA0005119549630000271
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer composite materials, and particularly relates to a PC / ABS composite material with high heat resistance and flame retardance as well as a preparation method and application of the PC / ABS composite material. The PC / ABS composite material is prepared from the following components in percentage by mass: 80 to 95 parts of polycarbonate resin, 5 to 20 parts of acrylonitrile-butadiene-styrene copolymer resin, 4 to 16 parts of a phosphorus flame retardant, 0.1 to 0.5 part of a sulfonate flame retardant, 2 to 8 parts of a compatilizer and 0.1 to 1 part of an antioxidant. According to the invention, sulfonate is compounded to synergistically generate BDP flame-retardant PC / ABS, so that the heat resistance of the material is remarkably improved, and the material shows excellent performance in the PC / ABS material. The heat stability and the mechanical performance of the material are remarkably improved through the optimized component proportion, and the material is suitable for application occasions with high flame retardance, low smoke and low toxicity, especially for products exposed outdoors for a long time such as new energy automobile charging piles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials, and specifically relates to a highly heat-resistant and flame-retardant PC / ABS composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the new energy vehicle industry, charging piles, as key supporting facilities, have put forward higher requirements for their materials. Charging pile materials not only need to have excellent mechanical properties and weather resistance, but also good flame retardant properties to ensure safety during use. Composite materials of polycarbonate (PC) and acrylonitrile-butadiene-styrene copolymer (ABS) are widely used in various engineering plastics fields with high performance requirements due to their superior comprehensive performance. However, the flame retardancy of ABS is poor and effective flame retardant modification is required.

[0003] Phosphorus-based flame retardants such as bisphenol A-bis(diphenyl phosphate) (BDP) are widely used in flame retardant modification of PC / ABS. It has high thermal stability, can maintain structural integrity at high temperatures, and forms a stable protective layer in the condensed phase to block the transfer of heat and oxygen and delay the combustion process. However, when BDP is used alone, it may cause dripping and high smoke concentration when the material is burned, affecting its safety. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a highly heat-resistant and flame-retardant PC / ABS composite material and its preparation method and application. By compounding the phosphorus-based flame retardant and the sulfonate-based flame retardant, the synergistic effect of the two can be fully utilized to form a dense carbonized layer, block heat and oxygen, prevent further combustion of the material, reduce toxic smoke and dripping, and not only significantly improve the flame retardant properties of the material, but also maintain the mechanical properties and thermal stability of the material, ensuring the stability and durability of the energy vehicle charging pile in different environments.

[0005] The present invention solves the above technical problems through the following technical solutions.

[0006] The first object of the present invention is to provide a highly heat-resistant and flame-retardant PC / ABS composite material, which is prepared by the following components in percentage by weight: polycarbonate resin: 80 parts to 95 parts, acrylonitrile-butadiene-styrene copolymer resin: 5 parts to 20 parts, phosphorus-based flame retardant: 4 parts to 16 parts, sulfonate-based flame retardant: 0.1 parts to 0.5 parts, compatibilizer: 2 parts to 8 parts and antioxidant: 0.1 parts to 1 part.

[0007] Furthermore, the phosphorus-based flame retardant is bisphenol A diphenyl phosphate.

[0008] Furthermore, the sulfonate flame retardant is prepared by mixing sodium p-toluenesulfonate, sodium dodecylsulfonate and titanium phosphate in a mass ratio of 3 to 3.5:3 to 3.5:4.

[0009] Furthermore, the compatibilizer is one of maleic anhydride styrene binary random copolymer, styrene-acrylonitrile-glycidyl methacrylate ternary random copolymer, and maleic anhydride grafted hydrogenated styrene-butadiene-styrene block copolymer.

[0010] Furthermore, the antioxidant is any two combinations of hindered phenol antioxidant 1010, hindered phenol antioxidant 1076, phosphite antioxidant 168, phosphite antioxidant 626, and thioester antioxidant.

[0011] Furthermore, the polycarbonate resin has a melt flow rate of 5 g / 10 min to 10 g / 10 min, and a relative molecular mass of 30,000 g / mol to 40,000 g / mol.

[0012] Furthermore, the melt flow rate of the acrylonitrile-butadiene-styrene copolymer resin is 15 g / 10 min to 25 g / 10 min, and the relative molecular mass is 100,000 g / mol to 150,000 g / mol.

[0013] A second object of the present invention is to provide a method for preparing the above-mentioned high heat-resistant flame-retardant PC / ABS composite material, comprising the following steps:

[0014] The polycarbonate resin and the acrylonitrile-butadiene-styrene copolymer resin are dried at 80° C. to 100° C. for 2 h to 6 h and set aside.

[0015] Weigh the components according to their mass proportions: 80 to 95 parts of polycarbonate resin, 5 to 20 parts of acrylonitrile-butadiene-styrene copolymer resin, 4 to 16 parts of phosphorus-based flame retardant, 0.1 to 0.5 parts of sulfonate-based flame retardant, 2 to 8 parts of compatibilizer and 0.1 to 1 part of antioxidant, stir and mix until coated to obtain a mixture.

[0016] The mixed material is put into an extrusion granulator for melt extrusion, cooling and pelletizing to obtain a high-strength and high-toughness PC / ABS composite material.

[0017] Furthermore, the temperature settings of each zone of the extrusion granulator are 180℃~270℃ for zone 1, 180℃~270℃ for zone 2, 180℃~270℃ for zone 3, 220℃~280℃ for zone 4, 220℃~270℃ for zone 5, 220℃~270℃ for zone 6, 220℃~270℃ for zone 7, 220℃~270℃ for zone 8, 220℃~270℃ for zone 9, 220℃~270℃ for zone 10, and 220℃~270℃ for zone 11, and the extrusion speed is 200r / min~600r / min.

[0018] The third object of the present invention is to provide the above-mentioned high-strength and high-toughness PC / ABS composite material for use in preparing charging pile casings.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention uses a compound of phosphorus-based flame retardants and sulfonate-based flame retardants to give full play to the synergistic effect of the two, make up for each other's shortcomings, enhance the flame retardant effect of the condensed phase, form a dense carbonized layer, block heat and oxygen, prevent further combustion of the material, and reduce toxic smoke and dripping; the cross-linking reaction promoted by the sulfonate can effectively reduce the dripping of the material during combustion and the generation of toxic smoke, thereby improving the safety of the material. The combination of phosphorus-based flame retardants and sulfonates can not only significantly improve the flame retardant properties of the material, but also maintain the mechanical properties and thermal stability of the material, thereby ensuring the stability and durability of the energy vehicle charging pile in different environments.

[0021] (2) The sulfonate flame retardant used in the present invention decomposes to produce a small amount of alkyl salt under the combustion conditions of the composite material, promotes the rearrangement isomerization reaction of the polycarbonate chain, generates a large amount of non-combustibles such as carbon dioxide and water, and reduces the concentration of combustible gas. In addition, the sulfonate flame retardant can also be used as a catalyst for the transesterification reaction of polycarbonate under pyrolysis conditions, promotes the cross-linking of the material into carbon, and enhances the condensed phase flame retardant effect. Through the catalytic effect of the sulfonate flame retardant, the material is promoted to generate a large amount of non-combustibles during the combustion process, reduces the concentration of combustible gas, and improves the flame retardant effect.

[0022] (3) The present invention optimizes the melt flow rate and relative molecular weight of PC and ABS resins to prepare a composite material that exhibits excellent performance in terms of tensile strength, elongation at break, flexural strength, elastic modulus, impact strength and heat deformation temperature. It not only improves the flame retardant properties of PC / ABS, but also maintains the mechanical properties and transparency of the material, and has the advantages of good self-extinguishing properties and low addition amount. The test results show that the composite material meets the UL94 V-0 flame retardant standard at a thickness of 1.6 mm. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0025] Phosphorus-based flame retardants such as bisphenol A-bis(diphenyl phosphate) (BDP) are widely used in the flame retardant modification of PC / ABS. It has high thermal stability, can maintain structural integrity at high temperatures, and form a stable protective layer in the condensed phase to block the transfer of heat and oxygen and delay the combustion process. However, when BDP is used alone, it may cause dripping and high smoke concentration when the material burns, affecting its safety. Sulfonate-based flame retardants, as a type of high-efficiency flame retardant, are mostly used in polymer materials and perform well in improving the flame retardant properties of PC. However, when used alone, they also have a certain effect on the transparency and mechanical properties of the material.

[0026] Based on the above problems, the present invention provides a highly heat-resistant and flame-retardant PC / ABS composite material, which is prepared by the following components in percentage by weight: polycarbonate resin: 80 to 95 parts, acrylonitrile-butadiene-styrene copolymer resin: 5 to 20 parts, phosphorus-based flame retardant: 4 to 16 parts, sulfonate-based flame retardant: 0.1 to 0.5 parts, compatibilizer: 2 to 8 parts and antioxidant: 0.1 to 1 part.

[0027] The present invention uses a compound of a phosphorus-based flame retardant and a sulfonate-based flame retardant to give full play to the synergistic effect of the two, make up for each other's shortcomings, enhance the flame retardant effect of the condensed phase, form a dense carbonized layer, block heat and oxygen, prevent further combustion of the material, and reduce toxic smoke and dripping; the cross-linking reaction promoted by the sulfonate can effectively reduce the dripping of the material during combustion and the generation of toxic smoke, thereby improving the safety of the material. The combination of the phosphorus-based flame retardant and the sulfonate can not only significantly improve the flame retardant performance of the material, but also maintain the mechanical properties and thermal stability of the material, thereby ensuring the stability and durability of the energy vehicle charging pile in different environments.

[0028] In a specific embodiment, the phosphorus flame retardant is bisphenol A diphenyl phosphate (BDP). BDP has high thermal stability, can maintain structural integrity at high temperatures, and forms a stable protective layer in the condensed phase to block the transfer of heat and oxygen and delay the combustion process. However, when BDP is used alone, it may cause the material to drip and produce a high smoke concentration during combustion, affecting the safety of use. The present invention uses BDP and sulfonate flame retardants in combination, with the purpose of improving the dripping phenomenon and high smoke concentration produced by BDP during combustion through sulfonate flame retardants. By compounding sulfonate flame retardants and BDP, a dense carbonized layer can be formed to block heat and oxygen, prevent further combustion of materials, and reduce toxic smoke and dripping.

[0029] In a specific embodiment, the sulfonate flame retardant is a mixture of sodium p-toluenesulfonate, sodium dodecylsulfonate and titanium phosphate in a mass ratio of 3 to 3.5:3 to 3.5:4.

[0030] Among them, sodium p-toluenesulfonate provides basic flame retardant effect, sodium dodecylsulfonate provides surface activity and further flame retardant performance, and titanium phosphate enhances high temperature protection to prevent flame spread, and then compound the prepared composite sulfonate flame retardant. Among them, the three sulfonates can play a synergistic flame retardant role. Sodium dodecylsulfonate, as a surfactant, can make sodium toluenesulfonate and titanium phosphate produce physical interaction, so that the sulfonate flame retardant is evenly distributed in the substrate. Sodium dodecylbenzenesulfonate can establish a balanced system with sodium toluenesulfonate and titanium phosphate, which has a better flame retardant effect. Among the sulfonate flame retardants, the compounded sulfonate flame retardant decomposes under the combustion conditions of the composite material to produce a small amount of alkyl salt, promotes the rearrangement isomerization reaction of the polycarbonate chain, generates a large amount of non-combustibles such as carbon dioxide and water, and reduces the concentration of combustible gas. In addition, sulfonate flame retardants can also be used as catalysts for polycarbonate transesterification reactions under pyrolysis conditions, promoting the cross-linking of materials into carbon and enhancing the flame retardant effect of the condensed phase. Through the catalytic action of sulfonate flame retardants, the materials are promoted to generate a large amount of non-combustibles during the combustion process, reducing the concentration of combustible gases and improving the flame retardant effect.

[0031] In a specific embodiment, the compatibilizer is one of maleic anhydride styrene binary random copolymer (MAH-PS), styrene-acrylonitrile-glycidyl methacrylate ternary random copolymer (SAN-MMA-GMA), and maleic anhydride grafted hydrogenated styrene-butadiene-styrene block copolymer (MAH-g-HSBS). The compatibility of the composite material can be improved, and the toughness of the composite material can be increased, and the impact strength and mechanical properties can be improved.

[0032] In a specific embodiment, the antioxidant is any two combinations of hindered phenol antioxidant 1010, hindered phenol antioxidant 1076, phosphite antioxidant 168, phosphite antioxidant 626, and thioester antioxidant.

[0033] In a specific embodiment, the melt flow rate of the polycarbonate resin is 5g / 10min-10g / 10min, and the relative molecular mass is 30000g / mol-40000g / mol. The melt flow rate of the acrylonitrile-butadiene-styrene copolymer resin is 15g / 10min-25g / 10min, and the relative molecular mass is 100000g / mol-150000g / mol. By optimizing the melt flow rate and relative molecular mass of PC and ABS resins, the prepared composite material shows excellent performance in terms of tensile strength, elongation at break, flexural strength, elastic modulus, impact strength and heat deformation temperature. The test results show that the composite material meets the UL94 V-0 flame retardant standard at a thickness of 1.6mm.

[0034] The present invention also provides a method for preparing the above-mentioned highly heat-resistant and flame-retardant PC / ABS composite material, comprising the following steps:

[0035] The polycarbonate resin and the acrylonitrile-butadiene-styrene copolymer resin are dried at 80° C. to 100° C. for 2 h to 6 h and set aside.

[0036] Weigh each component according to the mass proportion: polycarbonate resin: 80 parts to 95 parts, acrylonitrile-butadiene-styrene copolymer resin: 5 parts to 20 parts, phosphorus-based flame retardant: 4 parts to 16 parts, sulfonate-based flame retardant: 0.1 parts to 0.5 parts, compatibilizer: 2 parts to 8 parts, antioxidant: 0.1 parts to 1 parts, stir and mix until coated to obtain a mixture.

[0037] The mixed material is put into an extrusion granulator for melt extrusion, cooling and pelletizing to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0038] In a specific embodiment, the temperature settings of each zone of the extrusion granulator are 180°C ~ 270°C for zone 1, 180°C ~ 270°C for zone 2, 180°C ~ 270°C for zone 3, 220°C ~ 280°C for zone 4, 220°C ~ 270°C for zone 5, 220°C ~ 270°C for zone 6, 220°C ~ 270°C for zone 7, 220°C ~ 270°C for zone 8, 220°C ~ 270°C for zone 9, 220°C ~ 270°C for zone 10, and 220°C ~ 270°C for zone 11, and the extrusion speed is 200r / min ~ 600r / min.

[0039] In melt extrusion, a twin-screw extruder can be used to adapt to different production scales and efficiency requirements; in the cooling and pelletizing process, water cooling or air cooling can be used to adapt to different production environments. By compounding sulfonate to synergize BDP flame retardant PC / ABS, the heat resistance of the material is significantly improved, making it exhibit excellent performance in PC / ABS materials. The optimized component ratio significantly improves the thermal stability and mechanical properties of the material, making it suitable for applications with high flame retardancy, low smoke, and low toxicity, especially in products such as new energy vehicle charging piles that are exposed to the outdoors for a long time.

[0040] The invention is further described below through specific examples.

[0041] Example 1

[0042] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0043] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0044] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0045] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0046] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0047] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0048] Example 2

[0049] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0050] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is Chimei 110, with a melt flow rate of 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Formosa Chemical ABSDG417, with a melt flow rate of 20g / 10min. The bisphenol A diphenyl phosphate is Aidico FP-600.

[0051] The antioxidant is compounded with hindered phenol antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 1:1.

[0052] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0053] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0054] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0055] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0056] Example 3

[0057] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0058] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS121H, and the melt flow rate is 25g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0059] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0060] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0061] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0062] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0063] Example 4

[0064] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0065] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is SABIC PC 1414, and the melt flow rate is 15g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0066] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0067] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0068] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0069] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0070] Example 5

[0071] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0072] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The model of carbonate resin is SABIC PC 1414, and the melt flow rate is 15g / 10min. The model of acrylonitrile-butadiene-styrene copolymer resin is Formosa Chemical ABSDG417, and the melt flow rate is 20g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is compounded with hindered phenol antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 1:1.

[0073] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0074] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0075] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0076] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0077] Example 6

[0078] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0079] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is SABIC PC 1414, with a melt flow rate of 15g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS121H, with a melt flow rate of 25g / 10min. The bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0080] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0081] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0082] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0083] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0084] Example 7

[0085] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0086] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is SABIC PC 1609-11, and the melt flow rate is 10g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0087] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0088] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0089] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0090] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0091] Example 8

[0092] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0093] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The model of carbonate resin is Formosa Chemical ABSDG417, and the melt flow rate is 20g / 10min. The model of acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0094] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0095] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0096] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0097] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0098] Example 9

[0099] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0100] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is SABIC PC 1609-11, and the melt flow rate is 10g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS121H, and the melt flow rate is 25g / 10min. The bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0101] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0102] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0103] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0104] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0105] Example 10

[0106] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 60 parts of polycarbonate resin, 40 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of compatibilizer maleic anhydride styrene binary random copolymer, and 0.3 parts of antioxidant.

[0107] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0108] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0109] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0110] S2. Weigh each component according to the mass fraction: polycarbonate resin: 60 parts, acrylonitrile-butadiene-styrene copolymer resin: 40 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0111] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0112] Embodiment 11

[0113] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 70 parts of polycarbonate resin, 30 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of compatibilizer maleic anhydride styrene binary random copolymer, and 0.3 parts of antioxidant.

[0114] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0115] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0116] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0117] S2. Weigh each component according to the mass fraction: polycarbonate resin: 70 parts, acrylonitrile-butadiene-styrene copolymer resin: 30 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0118] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0119] Example 12

[0120] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 80 parts of polycarbonate resin, 20 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of compatibilizer maleic anhydride styrene binary random copolymer, and 0.3 parts of antioxidant.

[0121] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0122] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0123] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0124] S2. Weigh each component according to the mass fraction: polycarbonate resin: 80 parts, acrylonitrile-butadiene-styrene copolymer resin: 20 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0125] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0126] Embodiment 13

[0127] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 95 parts of polycarbonate resin, 5 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0128] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0129] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0130] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0131] S2. Weigh each component according to the mass fraction: polycarbonate resin: 95 parts, acrylonitrile-butadiene-styrene copolymer resin: 5 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0132] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0133] Embodiment 14

[0134] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of a compatibilizer ternary random copolymer of styrene-acrylonitrile-glycidyl methacrylate (SAN-MMA-GMA), and 0.3 parts of an antioxidant.

[0135] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0136] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0137] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0138] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0139] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0140] Embodiment 15

[0141] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of compatibilizer maleic anhydride grafted hydrogenated styrene-butadiene-styrene block copolymer (MAH-g-HSBS), and 0.3 parts of antioxidant.

[0142] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0143] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0144] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0145] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0146] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0147] Example 16

[0148] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0149] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3.5:3.5:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0150] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0151] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0152] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0153] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0154] Embodiment 17

[0155] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of a compatibilizer ternary random copolymer of styrene-acrylonitrile-glycidyl methacrylate (SAN-MMA-GMA), and 0.3 parts of an antioxidant.

[0156] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3.5:3.5:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0157] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0158] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0159] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer styrene-acrylonitrile-methacrylate glycidyl ternary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0160] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0161] Embodiment 18

[0162] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0163] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate, sodium dodecyl sulfonate and titanium phosphate in a mass ratio of 3:3:4. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The model of bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1076 and a thioester antioxidant DSTDP in a mass ratio of 1:1.

[0164] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0165] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0166] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0167] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0168] Comparative Example 1

[0169] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 6 parts of a compatibilizer maleic anhydride styrene binary random copolymer, and 0.3 parts of an antioxidant.

[0170] The carbonate resin is Chimei 110 with a melt flow rate of 6 g / 10 min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k with a melt flow rate of 15 g / 10 min. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0171] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0172] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0173] S2. Weigh each component according to the mass fraction: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant, and stir and mix them evenly to obtain a mixture.

[0174] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0175] Comparative Example 2

[0176] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 6 parts of a compatibilizer maleic anhydride styrene binary random copolymer, and 0.3 parts of an antioxidant.

[0177] The carbonate resin is Chimei 110 with a melt flow rate of 6 g / 10 min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k with a melt flow rate of 15 g / 10 min. The bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is compounded with hindered phenol antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 1:1.

[0178] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0179] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0180] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0181] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0182] Comparative Example 3

[0183] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0184] Among them, the sulfonate flame retardant is a mixture of sodium toluene sulfonate and sodium dodecyl sulfonate in a mass ratio of 1:1. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168 in a mass ratio of 1:1.

[0185] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0186] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0187] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0188] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0189] Comparative Example 4

[0190] A highly heat-resistant and flame-retardant PC / ABS composite material is prepared from the following components in percentage by mass: 90 parts of polycarbonate resin, 10 parts of acrylonitrile-butadiene-styrene copolymer resin, 11.2 parts of bisphenol A diphenyl phosphate, 0.8 parts of sulfonate flame retardant, 6 parts of maleic anhydride styrene binary random copolymer as a compatibilizer, and 0.3 parts of antioxidant.

[0191] Among them, the sulfonate flame retardant is sodium toluene sulfonate. The carbonate resin is Chimei 110, and the melt flow rate is 6g / 10min. The acrylonitrile-butadiene-styrene copolymer resin is Chimei ABS 757k, and the melt flow rate is 15g / 10min. The bisphenol A diphenyl phosphate is Aidico FP-600. The antioxidant is compounded with hindered phenol antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 1:1.

[0192] The preparation method of the above-mentioned high heat-resistant flame-retardant PC / ABS composite material comprises the following steps:

[0193] S1. Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 3 h and set aside.

[0194] S2. Weigh each component according to the mass fraction: polycarbonate resin: 90 parts, acrylonitrile-butadiene-styrene copolymer resin: 10 parts, bisphenol A diphenyl phosphate: 11.2 parts, sulfonate flame retardant: 0.8 parts, compatibilizer maleic anhydride styrene binary random copolymer: 6 parts, antioxidant: 0.3 parts, stir and mix until coated to obtain a mixture.

[0195] S3. The mixed material is put into a twin-screw extruder for melt extrusion. The temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11. The extrusion speed is 240r / min. After extrusion, the mixture is water cooled, dried and pelletized to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

[0196] The properties of the PC / ABS composite material particles prepared in Example 1 to Example 18 and Comparative Example 1 to Comparative Example 4 were tested, wherein the tensile properties were tested according to GB1040-92, the tensile properties were tested according to GB1040-92, the bending properties were tested according to GB / T9341-2000, the impact properties were tested according to GB / T1843-2008, the limiting oxygen index was tested according to GBT 2406.22009, and the flame retardant properties were tested according to UL94-2013 standard. The results are shown in Table 1.

[0197] Table 1 Mechanical properties of PC / ABS composite materials prepared in Example 1 to Example 18 and Comparative Example 1

[0198]

[0199]

[0200] As shown in Table 1, it can be seen from Examples 1 to 9 that the use of high viscosity PC and ABS with low melt flow rate can improve the impact strength of the prepared PC / ABS composite material. The impact strength in Example 1 can reach 54.4 kJ. 2 / m, in Examples 10 to 13, the increase in the PC:ABS ratio will increase the heat deformation temperature of the PC / ABS composite material, and the heat deformation temperature in Example 13 can reach 124.5°C.

[0201] The present invention optimizes the melt flow rate and relative molecular weight of PC and ABS resins to prepare a composite material that exhibits excellent performance in terms of tensile strength, elongation at break, flexural strength, elastic modulus, impact strength, and heat deformation temperature. Test results show that the composite material meets the UL94 V-0 flame retardant standard at a thickness of 1.6 mm.

[0202] It can be seen from Comparative Examples 1 to 4 that without adding any flame retardant, the limiting oxygen index of the PC / ABS composite material is only 25.4%, and the flame retardant grade is V2. After adding BDP, the flame retardant effect is effectively improved. When only one type of sulfonate sodium toluene sulfonate and two compound sulfonates of sodium toluene sulfonate and sodium dodecyl sulfonate are added as flame retardants, the flame retardant effect can only reach V1. Compared with the PC / ABS composite material with the addition of BDP and three sulfonate compound flame retardants at the same time, the addition of the prepared compound sulfonate effectively increases the heat deformation temperature of the material from 95.2°C to 120.1°C. The addition of sulfonates improves the rigidity and heat resistance of the material.

[0203] The present invention uses a compound of a phosphorus-based flame retardant and a sulfonate-based flame retardant to give full play to the synergistic effect of the two, make up for each other's shortcomings, enhance the flame retardant effect of the condensed phase, form a dense carbonized layer, block heat and oxygen, prevent further combustion of the material, and reduce toxic smoke and dripping; the cross-linking reaction promoted by the sulfonate can effectively reduce the dripping of the material during combustion and the generation of toxic smoke, thereby improving the safety of the material. The combination of the phosphorus-based flame retardant and the sulfonate can not only significantly improve the flame retardant performance of the material, but also maintain the mechanical properties and thermal stability of the material, thereby ensuring the stability and durability of the energy vehicle charging pile in different environments.

[0204] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0205] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A highly heat-resistant and flame-retardant PC / ABS composite material, characterized in that: The invention is prepared by the following components in percentage by weight: polycarbonate resin: 80 to 95 parts, acrylonitrile-butadiene-styrene copolymer resin: 5 to 20 parts, phosphorus-based flame retardant: 4 to 16 parts, sulfonate-based flame retardant: 0.1 to 0.5 parts, compatibilizer: 2 to 8 parts and antioxidant: 0.1 to 1 part.

2. The highly heat-resistant and flame-retardant PC / ABS composite material according to claim 1, characterized in that: The phosphorus-based flame retardant is bisphenol A-bis(diphenyl phosphate).

3. The highly heat-resistant and flame-retardant PC / ABS composite material according to claim 1, characterized in that: The sulfonate flame retardant is prepared by mixing sodium p-toluenesulfonate, sodium dodecylsulfonate and titanium phosphate in a mass ratio of 3 to 3.5:3 to 3.5:

4.

4. The highly heat-resistant and flame-retardant PC / ABS composite material according to claim 1, characterized in that: The compatibilizer is one of maleic anhydride styrene binary random copolymer, styrene-acrylonitrile-glycidyl methacrylate ternary random copolymer, and maleic anhydride grafted hydrogenated styrene-butadiene-styrene block copolymer.

5. The highly heat-resistant and flame-retardant PC / ABS composite material according to claim 1, characterized in that: The antioxidant is any combination of two of the hindered phenol antioxidant 1010, the hindered phenol antioxidant 1076, the phosphite antioxidant 168, the phosphite antioxidant 626, and the thioester antioxidant.

6. The highly heat-resistant and flame-retardant PC / ABS composite material according to claim 1, characterized in that: The polycarbonate resin has a melt flow rate of 5 g / 10 min to 10 g / 10 min, and a relative molecular mass of 30000 g / mol to 40000 g / mol.

7. The highly heat-resistant and flame-retardant PC / ABS composite material according to claim 1, characterized in that: The melt flow rate of the acrylonitrile-butadiene-styrene copolymer resin is 15 g / 10 min to 25 g / 10 min, and the relative molecular mass is 100000 g / mol to 150000 g / mol.

8. A method for preparing the highly heat-resistant and flame-retardant PC / ABS composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polycarbonate resin and the acrylonitrile-butadiene-styrene copolymer resin are dried at 80° C. to 100° C. for 2 h to 6 h and set aside; Weigh the components according to mass proportions, including 80 to 95 parts of polycarbonate resin, 5 to 20 parts of acrylonitrile-butadiene-styrene copolymer resin, 4 to 16 parts of phosphorus flame retardant, 0.1 to 0.5 parts of sulfonate flame retardant, 2 to 8 parts of compatibilizer and 0.1 to 1 part of antioxidant, stir and mix until coated to obtain a mixture; The mixed material is put into an extrusion granulator for melt extrusion, cooling and pelletizing to obtain a highly heat-resistant and flame-retardant PC / ABS composite material.

9. The method for preparing the highly heat-resistant and flame-retardant PC / ABS composite material according to claim 8, characterized in that: The temperature settings of each zone of the extrusion granulator are as follows: zone 1 temperature 180℃~270℃, zone 2 temperature 180℃~270℃, zone 3 temperature 180℃~270℃, zone 4 temperature 220℃~280℃, zone 5 temperature 220℃~270℃, zone 6 temperature 220℃~270℃, zone 7 temperature 220℃~270℃, zone 8 temperature 220℃~270℃, zone 9 temperature 220℃~270℃, zone 10 temperature 220℃~270℃, zone 11 temperature 220℃~270℃, and the extrusion speed is 200r / min~600r / min.

10. Use of the highly heat-resistant and flame-retardant PC / ABS composite material according to any one of claims 1 to 7 in preparing a charging pile shell.

Citation Information

Cited By

  • Anti-stress anti-coating bottom-biting PC / ABS (polycarbonate / acrylonitrile butadiene styrene) composite material and preparation method thereof

    CN120025676A

  • High-strength flame-retardant PCABS material and preparation method thereof

    CN121045791A